PENERAPAN STRATEGI LEARNING START WITH A QUESTION (LSQ) DALAM PEMBELAJARAN AKIDAH AKHLAK DI MAN - Ardilla, Verawati (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Learning of creed and morals is expected to encourage students to be actively involved in the learning process. To realize this, it is necessary to implement appropriate learning strategies. This study aims to analyze the implementation of the Learning Start With a Question strategy in learning Creed and Morals at MAN. The study used a qualitative descriptive method with data collection techniques through observation, interviews, and documentation, involving teachers, principals, and students as data sources. The results of the study showed that teachers had designed a good Learning Implementation Plan (RPP), but implementation in the classroom was not yet fully optimal. The results of this study concluded that the Learning Start With a Question strategy was effective in increasing student activity although it required further optimization in its implementation.